Stress Relaxation and Composition of Hydrazone‐Crosslinked Hybrid Biopolymer‐Synthetic Hydrogels Determine Spreading and Secretory Properties of MSCs (Adv. Healthcare Mater. 14/2022). Issue 14 (20th July 2022) - Borelli, Alexandra N.; Young, Mark W.; Kirkpatrick, Bruce E.; Jaeschke, Matthew W.; Mellett, Sarah; Porter, Seth; Blatchley, Michael R.; Rao, Varsha V.; Sridhar, Balaji V.; Anseth, Kristi S.
Abstract : Mesenchymal Stromal Cells Mesenchymal stromal cells (MSCs) are bone‐marrow derived stem cells isolated for culture in vitro or in vivo. In article number 2200393 by Kristi S. Anseth and co‐workers, MSCs are cultured in vitro, where the red stain, rhodamine phalloidin, visualizes the cell‐membrane, and the blue stain, DAPI, visualizes the cell nuclei. This image shows the ability of MSCs to cluster within a stress‐relaxing 3D environment.